The Influence of Job Stress, Job Satisfaction, and Work Motivation on Employee Performance at Muhammad Zein Regional Hospital, East Belitung: inggris - Ezdwima Putrisia, Ezdwima Putrisia; Ignatius Soni Kurniawan; Eko Yulianto (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This research is motivated by the importance of improving the performance of Muhammad Zein Belitung Timur Regional Hospital employees which is influenced by job stress, job satisfaction, and work motivation. The purpose of this study is to analyze the influence of job stress, job satisfaction, and work motivation on the performance of Muhammad Zein Belitung Timur Regional Hospital employees, especially in the administration and skilled nurse divisions. This research is a quantitative study that uses census techniques in determining respondents. Data distribution uses questionnaires directly to administrative employees and skilled nurses. The data obtained are processed using SmartPLS 4. The results of this study indicate that job stress has a positive but insignificant effect on employee performance, job satisfaction has a positive and significant but weak effect on employee performance, work motivation has a positive and significant effect on employee performance. The implications of this study indicate that improving employee performance can be achieved through increasing motivation and job satisfaction. Management needs to create a supportive work environment, provide appropriate rewards, and manage work stress so as not to hinder employee productivity.